Rural Healthy People 2020: New Decade, Same Challenges. Issue 3 (7th May 2015) - Bolin, Jane N.; Bellamy, Gail R.; Ferdinand, Alva O.; Vuong, Ann M.; Kash, Bita A.; Schulze, Avery; Helduser, Janet W.
Abstract Purpose The health of rural America is more important than ever to the health of the United States and the world. Rural Healthy People 2020's goal is to serve as a counterpart to Healthy People 2020, providing evidence of rural stakeholders' assessment of rural health priorities and allowing national and state rural stakeholders to reflect on and measure progress in meeting those goals. The specific aim of the Rural Healthy People 2020 national survey was to identify rural health priorities from among the Healthy People 2020's (HP2020) national priorities. Methods Rural health stakeholders (n = 1, 214) responded to a nationally disseminated web survey soliciting identification of the top 10 rural health priorities from among the HP2020 priorities. Stakeholders were also asked to identify objectives within each national HP2020 priority and express concerns or additional responses. Findings and Conclusions Rural health priorities have changed little in the last decade. Access to health care continues to be the most frequently identified rural health priority. Within this priority, emergency services, primary care, and insurance generate the most concern. A total of 926 respondents identified access as the no. 1 rural health priority, followed by, no. 2 nutrition and weight status (n = 661), no. 3 diabetes (n = 660), no. 4 mental health and mental disorders (n = 651), no. 5 substance abuse (n = 551), no. 6 heart disease and stroke (n = 550), no. 7 physical activity and health (n = 542), no. 8 older adults (n = 482), no. 9 maternal infant and child health (n = 449), and no. 10 tobacco use (n = 429).